Perselingkuhan dalam Filsafat Hindu: Konflik Antara Kāma dan Dharma - Ni Luh Gede Wariati (Jayapangus Press, 2026)
Infidelity is a complex social phenomenon because it involves emotional, ethical, and spiritual dimensions simultaneously. This study is grounded in the growing number of conflicts in modern relationships that are often explained psychologically but rarely examined through a systematic Hindu philosophical framework. The research aims to analyze infidelity through the tension between kāma as the force of desire and dharma as the principle of moral responsibility, emphasizing its novelty in the systematic integration of the puruṣārtha framework (kāma–dharma–artha–mokṣa) with modern psychological theories of human needs in interpreting relational misconduct. The method employed is a qualitative literature study using a hermeneutic–philosophical analysis of classical Hindu texts such as the Bhagavad Gītā, Mahābhārata, and Rāmāyaṇa, combined with an interpretive dialogue with contemporary psychological literature on attachment, affective needs, and commitment. The findings indicate that infidelity arises from an imbalance in puruṣārtha orientation, where the pursuit of kāma is detached from dharma and self-regulation. Hindu mythological narratives illustrate consistent patterns of moral, social, and spiritual consequences when desire is not integrated with ethical responsibility. In conclusion, Hindu philosophy offers a relational ethical model that is not only normative but also reflective and transformational, providing a relevant foundation for developing educational and counseling approaches grounded in moral–spiritual awareness for modern interpersonal relationships.